2014
DOI: 10.1155/2014/345252
|View full text |Cite
|
Sign up to set email alerts
|

TcGenerator Development: Up-to-DateTcRecovery Technologies for Increasing the Effectiveness of

Abstract: A review on theMosources available today and on theTcgenerators developed up to date for increasing the effectiveness ofMoutilisation is performed in the format of detailed description of the features and technical performance of the technological groups of theMoproduction andTcrecovery. The latest results of the endeavour in this field are also surveyed in regard of the technical solution for overcoming the shortage ofMosupply. The technological topics are grouped and discussed in a way to reflect the similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 77 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…The presence of H 3 O + and Zr-OH in the ZBM was caused by the hydrolysis of Zr-Cl (Le 2014;So et al 2007). Zr-Cl bond was not observed in FTIR spectra, however, its presence was observed by So et al (2017) using thermal analysis and Awaludin et al (2015) using X-ray.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of H 3 O + and Zr-OH in the ZBM was caused by the hydrolysis of Zr-Cl (Le 2014;So et al 2007). Zr-Cl bond was not observed in FTIR spectra, however, its presence was observed by So et al (2017) using thermal analysis and Awaludin et al (2015) using X-ray.…”
Section: Resultsmentioning
confidence: 99%
“…Use of radioisotope concentrator in optimisation of the generator elution to increase 99m Tc-activity yield and effectiveness of 99 Mo utilisation [5,6] The radioisotope concentration process not only has positive impact on the extension of useful life time of the generators, but also is capable to increase the effectiveness of 99m Tc and 99 Mo utilisation by performing the early elutions of the generator at any time before maximal buildup of 99m Tc. The 99m Tc activity yield of the generator can be increased by performing an optimal regime of multiple ''early'' elutions (the generator is more frequently eluted) combined with a process of 99m Tc-eluate concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Note that enrichment refers to artificially increasing the amount of 98 Mo present in the target relative to the approximate Mo usually has 4 times higher 98 Mo atoms (up to fourfold for > 98% enrichment) compared to the natural Mo. It is reported that the specific activity of 99 Mo production with 8-day irradiation in a reactor with thermal flux 1.0 × 10 14 ncm −2 s −1 can reach the value of about 1.6 Ci 99 Mo/ g of natural and 6 Ci 99 Mo/g of enriched molybdenum target at the end of bombardment (EOB) [20].…”
Section: Neutron Activationmentioning
confidence: 99%
“…After 120 h of irradiation, the specific activity of 99 Mo was reported to be 16 GBq/g (~ 0.432 Ci/g) for enriched sample and 5 GBq/g (0.135 Ci/g) for natural sample. Yields of 99 Mo can be significantly enhanced by the epithermal neutron activation, hence the selection of the irradiation position is critical particularly in lower flux reactors [12,20]. Toth et al [22] reported that there are several factors such as self-shielding, parasitic absorption, and depletion of the product that must be accounted to identify the effective cross-section as these factors may change the results by 10 to 50%.…”
Section: Neutron Activationmentioning
confidence: 99%